2020
DOI: 10.1038/s41396-020-00826-5
|View full text |Cite
|
Sign up to set email alerts
|

Plant part and a steep environmental gradient predict plant microbial composition in a tropical watershed

Abstract: Plant microbiomes are shaped by forces working at different spatial scales. Environmental factors determine a pool of potential symbionts while host physiochemical factors influence how those microbes associate with distinct plant tissues. These scales are seldom considered simultaneously, despite their potential to interact. Here, we analyze epiphytic microbes from nine Hibiscus tiliaceus trees across a steep, but short, environmental gradient within a single Hawaiian watershed. At each location, we sampled e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 63 publications
5
21
2
Order By: Relevance
“…As we sampled only four trees per city, we may be overestimating the amount of core taxa defined per city and compartment. Nevertheless, our findings are in accordance with previous studies that included multiple plant compartments, as they also observed many shared bacterial taxa despite the consistent observations of different phyllosphere compartments harboring very distinct community compositions ( 27 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…As we sampled only four trees per city, we may be overestimating the amount of core taxa defined per city and compartment. Nevertheless, our findings are in accordance with previous studies that included multiple plant compartments, as they also observed many shared bacterial taxa despite the consistent observations of different phyllosphere compartments harboring very distinct community compositions ( 27 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…An important distinction in our study is that we sampled from the organic soil layer rather than leaf litter. Evidence from bacterial ( Bai et al, 2015 ; Zarraonaindia et al, 2015 ; Wagner et al, 2016 ) and fungal systems ( Amend et al, 2019 ; Bernard et al, 2021 ) have shown that soil may act as a reservoir of microbes that migrate to the phylloplane, an observation that is supported by our results ( Table 1 ).…”
Section: Discussionsupporting
confidence: 87%
“…Range size and niche breadth are positively correlated among plants and animals ( Slatyer, Hirst & Sexton, 2013 ; Bernard et al, 2021 ). Here we show that for fungi, niche breadth may or may not correlate with range size, and that this equivocal result depends on how range size is calculated ( Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations